Il trauma nella serialità televisiva di "Grey’s Anatomy" (Comparatismi, 2022)
The aim of this essay is to take into account how individual and collective traumas are shown through the new international media landscape, in particular through the US television series Grey’s Anatomy, conceived by Shonda Rhimes. At least for the 21st century, tv series have become the culturally hegemonic form of storytelling, proving to be able to tell very long stories and allowing the characters to evolve over a particularly long period of time. In addition to that, the tv series, entering the home of the user, have created a bond with him/her based on greater intimacy, which has allowed a narration of the trauma at deeper levels. Grey’s Anatomy will be the privileged object of this essay, because it faces, season after season, various collective traumas.